Pengaruh Minat dan Harga Terhadap Keputusan Pembelian Produk Tanaman Hias di Desa Banyuurip Kecamatan Kedamean Gresik - Nur Jannah Oryza Putri; Iswati Iswati; Anis Fitriyasari; Eny Sulistyowati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze the influence of interest and price on purchasing decisions for ornamental plant products at flower shops in Banyuurip village, Kedamean Gresik district. This type of research is quantitative using an explanatory approach. The data collection technique was carried out using a questionnaire which was distributed to 100 customers who had made purchase transactions at least twice at the flower stand in Banyuurip Village, Kedamean Gresik District. The data analysis technique used is multiple linear regression analysis t test, f test, classical assumptions, normality with the help of the SPSS program. The results of the research show that there is a positive and significant influence between purchasing interest and selling price on purchasing decisions for ornamental plant products at flower shops in Banyuurip village, Kedamean Gresik subdistrict.